Species delimitation in the Drosophila aldrichi subcluster (Diptera: Drosophilidae) using DNA sequences - Oliveira, Deodoro C. S. G.; Leonidas, Melissa; Etges, William J.; O’grady, Patrick M.; Desalle, Rob (Zootaxa, 2008)
DNA sequence data has been successfully used to verify current species-level taxonomic hypotheses based on morphology and other characters. Setting species boundaries in the Drosophila repleta group has been challenging because this group contains several cryptic taxa and morphologically polymorphic populations. Mitochondrial (cox1 and nad2) and nuclear (sina and Marf) genes were employed to assess species limits for two traditionally recognized, closely related, and taxonomically problematical species, D. aldrichi and D. wheeleri. Both tree-based and character-based methods were used to show that D. wheeleri is indeed a distinct species; however, our data shows that D. aldrichi is a paraphyletic assemblage of two lineages as previously suggested based on patterns of reproductive isolation. One lineage is sister to D. wheeleri and includes populations originating from southern and western Mexico (western-aldrichi). The second, basal group also contains flies from southern Mexico, along with populations from the northern and eastern regions within the species boundaries traditionally described as D. aldrichi (eastern-aldrichi). The populations of D. aldrichi that were introduced into Australia were found to be included in the eastern-aldrichi group. Our results, particularly those based on the rapidly evolving mtDNA sequences, confirm the presence of at least two cryptic species previously referred as “D. aldrichi”.